The transcriptional control of the VEGFA-VEGFR1 (FLT1) axis in alternatively polarized murine and human macrophages - Domokos, Apolka; Varga, Zsofia; Jambrovics, Karoly; Caballero-Sánchez, Noemí; Szabo, Eniko; Nagy, Gergely; Scholtz, Beata; Halasz, Laszlo; Varadi, Eszter; Bene, Krisztian P.; Mazlo, Anett; Bacsi, Attila; et al. (Frontiers in Immunology, 2023)
Macrophages significantly contribute to the regulation of vessel formation under physiological and pathological conditions. Although the angiogenesis-regulating role of alternatively polarized macrophages is quite controversial, a growing number of evidence shows that they can participate in the later phases of angiogenesis, including vessel sprouting and remodeling or regression. However, the epigenetic and transcriptional regulatory mechanisms controlling this angiogenesis-modulating program are not fully understood. Here we show that IL-4 can coordinately regulate the VEGFA-VEGFR1 (FLT1) axis via simultaneously inhibiting the proangiogenic Vegfa and inducing the antiangiogenic Flt1 expression in murine bone marrow-derived macrophages, which leads to the attenuated proangiogenic activity of alternatively polarized macrophages. The IL-4-activated STAT6 and IL-4-STAT6 signaling pathway-induced EGR2 transcription factors play a direct role in the transcriptional regulation of the Vegfa-Flt1 axis. We demonstrated that this phenomenon is not restricted to the murine bone marrow-derived macrophages, but can also be observed in different murine tissue-resident macrophages ex vivo and parasites-elicited macrophages in vivo with minor cell type-specific differences. Furthermore, IL-4 exposure can modulate the hypoxic response of genes in both murine and human macrophages leading to a blunted Vegfa/VEGFA and synergistically induced Flt1/FLT1 expression. Our findings establish that the IL-4-activated epigenetic and transcriptional program can determine angiogenesis-regulating properties in alternatively polarized macrophages under normoxic and hypoxic conditions.